METHODOLOGICAL APPROACHES AND MANAGEMENT METHODS FOR ENSURING ENERGY RESOURCE SUPPLY TO ENTERPRISES - Shuban, Mykhailo (Social Development: Economic and Legal Issues, 2025)
The relevance of the study is determined by the need to increase the efficiency of energy resource management in enterprises against the backdrop of rising energy costs, instability in the energy market, and the necessity to comply with environmental standards. It has been identified that modern energy supply systems require deep modernization, which includes digitalization, automation, and the integration of renewable energy sources. It has been established that without improving organizational and technical management mechanisms, enterprises lose a significant portion of their potential for resource savings. The purpose of the article is to analyze modern approaches to managing the energy supply of enterprises and to identify directions for their improvement, taking into account market, technological, and environmental challenges. The methods of systemic and comparative analysis were used to generalize energy management practices, a logical-analytical approach was applied to identify problems and barriers in the implementation of modern management methods, and elements of content analysis were employed to evaluate scientific and practical sources. Advanced international experience in energy system digitalization and the adaptation of ISO 50001 standards has been examined. It has been revealed that the key factors for improving management efficiency are the integrated use of IoT, digital twins, and automated forecasting systems. It has been proven that the combination of technological and organizational approaches ensures reduced energy consumption, minimizes the human factor, and increases the resilience of energy systems. It has been established that significant effects are achieved in practice through adaptive monitoring systems and the application of predictive models. An improved approach to the systematization of energy resource management methods has been developed, considering the industry-specific characteristics of enterprises. It has been proven that the effectiveness of energy system digitalization significantly increases with the integration of real-time analytics and the introduction of flexible demand management models. Key barriers to implementing modern management methods have been identified: worn-out infrastructure, high modernization costs, a lack of qualified personnel, and insufficient integration of digital solutions. Practical recommendations for improving efficiency have been substantiated through enhanced data analysis automation, the adaptation of international standards, and the improvement of organizational processes. Prospects for further research are associated with the development of comprehensive energy management models, the creation of methods for assessing the effectiveness of energy system digitalization, and the study of financial and economic mechanisms for supporting energy efficiency projects.